Clinical factors associated with microstructural connectome related brain dysmaturation in term neonates with congenital heart disease - Votava-Smith, Jodie K.; Gaesser, Jenna; Harbison, Anna Lonyai; Lee, Vince; Tran, Nhu; Rajagopalan, Vidya; del Castillo, Sylvia; Kumar, S. Ram; Herrup, Elizabeth; Baust, Tracy; Johnson, Jennifer A.; Gabriel, George C.; et al. (Frontiers in Neuroscience, 2022)
Objective: Term congenital heart disease (CHD) neonates display abnormalities of brain structure and maturation, which are possibly related to underlying patient factors and perioperative insults. Our primary goal was to delineate associations between clinical factors and postnatal brain microstructure in term CHD neonates using diffusion tensor imaging (DTI) magnetic resonance (MR) acquisition combined with complementary data-driven connectome and seed-based tractography quantitative analysis. Our secondary goal was to delineate associations between mild dysplastic structural abnormalities and connectome and seed-base tractography as our primary goal. Methods: Neonates undergoing cardiac surgery for CHD were prospectively recruited from two large centers. Both pre- and postoperative magnetic resonance (MR) brain scans were obtained. DTI in 42 directions was segmented to 90 regions using neonatal brain template and three weighted methods. Seed- based tractography was performed in parallel. Clinical data :18 patient-specific and 9 preoperative variables associated with preoperative scan and 6 intraoperative and 12 postoperative variables associated with postoperative scan. A composite Brain Dysplasia Score (BDS) was created including cerebellar, olfactory bulbs, and hippocampus abnormalities. The outcomes included (1) connectome metrics: cost and global/nodal efficiency (2) seed-based tractography: fractional anisotropy. Statistics: multiple regression with false discovery rate correction (FDR). Results: A total of 133 term neonates with complex CHD were prospectively enrolled and 110 had analyzable DTI. Multiple patient-specific factors including d-transposition of the great arteries physiology and severity of impairment of fetal cerebral substrate delivery were predictive of preoperative reduced cost (p<0.0073), reduced global/nodal efficiency (p <0.03). Multiple postoperative factors (extracorporeal membrane oxygenation [ECMO], seizures, cardiopulmonary resuscitation) were predictive of postoperative reduced cost, reduced global/nodal efficiency (p < 0.05). All three subcortical structures of the BDS (including olfactory bulb/sulcus, cerebellum, and hippocampus) predicted distinct patterns of altered nodal efficiency (p<0.05). Conclusion: Patient-specific and postoperative clinical factors were most predictive of diffuse postnatal microstructural dysmaturation in term CHD neonates. In contrast, subcortical components of a structurally based- brain dysplasia score, predicted more regional based postnatal microstructural differences. Collectively, these findings suggest that brain DTI connectome may facilitate deciphering the mechanistic relative contribution of clinical and genetic risk factors related to poor neurodevelopmental outcomes in CHD.